2012
DOI: 10.1111/j.1476-5381.2011.01639.x
|View full text |Cite
|
Sign up to set email alerts
|

Slow receptor dissociation is not a key factor in the duration of action of inhaled long‐acting β2‐adrenoceptor agonists

Abstract: BACKGROUND AND PURPOSEb2-Adrenoceptor agonists are important bronchodilators used for the treatment of chronic obstructive pulmonary disease and asthma. Clinical data on b2-adrenoceptor agonists show a range of onset and duration of action. We have investigated whether the receptor binding kinetics of b2-adrenoceptor agonists can explain their observed onset of action and duration of effect in the clinic. EXPERIMENTAL APPROACH KEY RESULTSThe clinically used b2-adrenoceptor agonists exhibited a range of associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
66
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 41 publications
10
66
0
Order By: Relevance
“…Therefore, in vitro receptor binding kinetics are only one factor in the process and cannot reliably predict the duration of effect of an administered compound (Fogarty et al, 2011). This is indeed the case for clinically relevant long-acting ␤ 2 -adrenoceptor agonists used in the treatment of COPD; t 1/2 values determined for indacaterol, a oncedaily ␤ 2 -adrenoceptor agonist (0.2 min), and salmeterol, a twicedaily ␤ 2 -adrenoceptor agonist (0.91 min), confirm that kinetic off rates from the ␤ 2 -adrenoceptor have no role to play in determining the duration of action of this class of molecule (Sykes and Charlton, 2012). Pharmacokinetic studies suggest that the systemic exposure achieved after inhalation of tiotropium and NVA237 is unlikely to produce functionally relevant occupancy Fig.…”
Section: Discussionmentioning
confidence: 69%
“…Therefore, in vitro receptor binding kinetics are only one factor in the process and cannot reliably predict the duration of effect of an administered compound (Fogarty et al, 2011). This is indeed the case for clinically relevant long-acting ␤ 2 -adrenoceptor agonists used in the treatment of COPD; t 1/2 values determined for indacaterol, a oncedaily ␤ 2 -adrenoceptor agonist (0.2 min), and salmeterol, a twicedaily ␤ 2 -adrenoceptor agonist (0.91 min), confirm that kinetic off rates from the ␤ 2 -adrenoceptor have no role to play in determining the duration of action of this class of molecule (Sykes and Charlton, 2012). Pharmacokinetic studies suggest that the systemic exposure achieved after inhalation of tiotropium and NVA237 is unlikely to produce functionally relevant occupancy Fig.…”
Section: Discussionmentioning
confidence: 69%
“…In addition to differing in chemical structure, these drugs also differ in binding affinity and intrinsic efficacy: Iso is classified as a full agonist and Sal as a higher affinity partial agonist (January et al, 1998;Nino et al, 2009). Furthermore, they exhibit distinct receptorbinding kinetics, with Sal having a much slower dissociation rate than Iso (Nials et al, 1993;Sykes and Charlton, 2012). Moreover, Sal drives b2-AR internalization less strongly than Iso (Moore et al, 2007) and is reported to be functionally selective, as indicated by a moderate b-arrestin bias (Rajagopal et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to isoprenaline and adrenaline (0.23 and 0.14 min, respectively) this represents the slowest dissociation rate we have observed for any β 2 adrenoceptor agonist tested to date (Sykes & Charlton, 2012). As C26 demonstrates slow dissociation from the…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that in the presence of a PDE inhibitor the cAMP generated by C26 was sustained for longer than either adrenaline or isoprenaline, which may suggest that C26 continues to promote cAMP generation over longer periods. The slow kinetic binding and signalling appear to be properties unique to C26, as other high affinity, long acting beta2 agonists have been shown to rapidly dissociate from the receptor (Sykes and Charlton, 2012). It is believed that for many of the LABAs such as salmeterol, the high lipophilicity of these compounds contributes to their long duration of action (Anderson et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation